Morphological and Mitochondrial Genomic Characterization of Eyeworms (Thelazia callipaeda) from Clinical Cases in Central China - Zhang, Xi; Shi, Ya L.; Wang, Zhong Q.; Duan, Jiang Y.; Jiang, Peng; Liu, Ruo D.; Cui, Jing (Frontiers in Microbiology, 2017)
Thelazia callipaeda, also called the oriental eyeworm, is the major etiological agent of human thelaziasis. Cases of thelaziasis have increased in recent years in China. Although this species is of medical importance, the genetics and phylogenetic systematics of T. callipaeda are poorly understood. In this study, we first reported three cases of thelaziasis in central China. All clinical isolates were identified as T. callipaeda according to morphological characteristics by light microscopy and scanning electron microscopy. Next, complete mitochondrial (mt) genomes for the three T. callipaeda isolates from different geographical locations were fully characterized using an Illumina sequencing platform. In addition, all available mt genomes of spirurid nematodes in GenBank were included to reconstruct the phylogeny and to explore the evolutionary histories of the isolates. The genome features of the T. callipaeda isolates contained 12 PCGs, 22 transfer RNA genes, two ribosomal RNA genes and a major non-coding region. The mtDNA nucleotide sequences of the T. callipaeda isolates from different hosts and different locations were similar. The nad6 gene showed high sequence variability among all isolates, which is worth considering for future population genetic studies of T. callipaeda. Phylogenetic analyses based on maximum parsimony (MP) and Bayesian inference (BI) methods revealed close relationships among Thelaziidae, Onchocercidae, Setariidae, Gongylonematidae, Physalopteridae, Dracunculidae and Philometridae. The monophyly of the T. callipaeda isolates from different hosts and distinct geographical locations was confirmed. The entire mt genomes of T. callipaeda presented in this study will serve as a useful dataset for studying the population genetics and phylogenetic relationships of Thelazia species.